Abrasion Resistance of Nano Silica Modified Roller Compacted Rubbercrete: Cantabro Loss Method and Response Surface Methodology Approach - Adamu, M. (Institute of Physics Publishing, 2018)
Roller compacted concrete (RCC) when used for pavement is subjected to skidding/rubbing by wheels of moving vehicles, this causes pavement surface to wear out and abrade. Therefore, abrasion resistance is one of the most important properties of concern for RCC pavement. In this study, response surface methodology was used to design, evaluate and analyze the effect of partial replacement of fine aggregate with crumb rubber, and addition of nano silica on the abrasion resistance of roller compacted rubbercrete (RCR). RCR is the terminology used for RCC pavement where crumb rubber was used as partial replacement to fine aggregate. The Box-Behnken design method was used to develop the mixtures combinations using 10, 20, and 30 crumb rubber with 0, 1, and 2 nano silica. The Cantabro loss method was used to measure the abrasion resistance. The results showed that the abrasion resistance of RCR decreases with increase in crumb rubber content, and increases with increase in addition of nano silica. The analysis of variance shows that the model developed using response surface methodology (RSM) has a very good degree of correlation, and can be used to predict the abrasion resistance of RCR with a percentage error of 5.44. The combination of 10.76 crumb rubber and 1.59 nano silica yielded the best combinations of RCR in terms of abrasion resistance of RCR. Â© 2018 Published under licence by IOP Publishing Ltd.